If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 6 + 1.5z Solving y = 6 + 1.5z Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 6 + 1.5z
| 7b-9=30 | | -25w3/42*-3w/10 | | 7(1/35x-2/7) | | x=120-(15x4)/(5x4) | | 7-2x=4x-3 | | (6)=7-4y | | X+2=18+8X-48 | | 3x+20=5x-10 | | 5-6y=6-7y | | -4-7-3x+4=24 | | 3.896-(-11.42)= | | n+8-6n=13 | | (6)-1=7-4y | | f(3/2)=2X-5 | | 3w+7=14+3x | | 3(m+1.5)=1.5 | | 2(6n-1)=-38 | | 3(2y+6)=-4[-3y-5(-y+10)] | | 2y-3z=12 | | 5(6x+1)=15 | | x-7/2-1=x-2/3 | | (6)-2=7-4y | | 6*3.14=2*3.14q | | 1.5x+3.6=2.7x | | (-2b+3)-5=-32-6b | | 7(4x+5)=-5+8(8x-4) | | 12f-14=4f+50 | | m/3.28=7.3 | | 2y+3z=12 | | X+48+5x-3= | | -2.5=p+7.2 | | r-d=y |